2010
DOI: 10.1507/endocrj.k10e-220
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of cell cycle progression by 2,3,7,8-tetrachlorodibenzo-p-dioxin eliciting ovulatory blockade in gonadotropin-primed immature rats

Abstract: 2,3,7,8-tetrachlorodibenzo-p-dioxin(TCDD or dioxin) is regarded as an endocrine-disrupting chemical with the ability to disrupt reproductive systems [1,2]. A single high dose of TCDD induces abortion, alters sexual behavior, decreases spermatogenesis and diminishes fertility [3][4][5][6]. In the rat, TCDD compromises ovarian follicular development and function including a premature transition to reproductive senescence [5] and a disruption of estrous cyclicity with prolonged periods of diestrus [7]. An acute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…A study on the ovulation rate in rats following TCDD exposure revealed that AhR ligand activation induces a G2/M cell cycle block resulting in a decrease in S-phase cells. This study also found that TCDD inhibits levels of Cdk2 and cyclin D2 [43]. The inhibitory effect has been seen with both genotoxic and non-gentoxic ligands for AhR.…”
Section: Discussionsupporting
confidence: 63%
“…A study on the ovulation rate in rats following TCDD exposure revealed that AhR ligand activation induces a G2/M cell cycle block resulting in a decrease in S-phase cells. This study also found that TCDD inhibits levels of Cdk2 and cyclin D2 [43]. The inhibitory effect has been seen with both genotoxic and non-gentoxic ligands for AhR.…”
Section: Discussionsupporting
confidence: 63%
“…In vitro studies revealed there are two binding sites for Rb within two distinct AhR domains and that association only occurs after AhR activation and translocation to the nucleus [61]. Also, TCDD has been shown to decrease levels of cyclin D to block cell cycle progression as well as interrupt the direct interaction between AhR and CKD4 [62]. Disruption of CDK4 interaction results in decreased phosphorylation of Rb and G1 cell cycle arrest [63].…”
Section: Discussionmentioning
confidence: 99%
“…The protein interactions range from transcription factors to coactivator and corepressor proteins. Reported interactions include, NFkB, COUP-TF1 and TFIIB [6264,68–70]. AhR and androgen receptor share a number of coactivator proteins such as SRC1 and p300 [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation combined with microarrays (ChIP-chip) and gene expression microarray experiments revealed that AHR regulates numerous genes involved in diverse cellular pathways, including metabolism and cellcycle regulation (8)(9)(10). In support of these findings, previous studies have shown that TCDD inhibits cell proliferation (11)(12)(13).…”
Section: Introductionmentioning
confidence: 72%